(untitled) (Raparin Journal of Humanities (RJH), 2023)
This study explored primary school teachers’ opinions on the effects of Flipped Learning (FL) depending on the grade level and subject matter taught in an EFL environment in Kurdistan. Teachers of a Bradost Private School in Raniyah participated in the study. Data were gathered by using a survey tool borrowed and modified by the researcher. 18 teachers participated randomly. Consequently, due to the additional technology needed outside of the classroom, the participants thought that certain students could find it challenging to access. The results show that the mean scores in the area of parent involvement and parent or teacher conferences, the participants strongly agreed that in an FL, video lectures make the class more transparent to parents, and they also believed that discussions with parents focused more on learning than they do on classroom behavior. Accordingly, they believed that time created for in-class activities in the FL allowed for more active learning and increased higher-order thinking for students, based on the following construct mean scores, with instructional considerations in the FL, in the areas of personalized learning, pupils to teacher interaction, active learning, and time for learning. They believe that FL gave teachers more time to improve and tailor education for students. Additionally, they cited favorable opinions of flipped learning in comparison to traditional classrooms.